2011
DOI: 10.1007/s00234-010-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with a self-expanding retrievable stent for recanalization of large vessel occlusions in acute ischemic stroke

Abstract: Use of a novel self-expanding, fully retrievable stent resulted in fast and very high recanalization rates in acute ischemic strokes with intravascular occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…[1][2][3][4][5] This improvement is reflected in better clinical outcome in studies such as Solitaire With the Intention for Thrombectomy (SWIFT), Thrombectomy Revascularization of Large Vessel Occlusions in Acute Ischemic Stroke (TREVO)-2, and Solitaire FR Thrombectomy for Acute Revascularization (STAR). [6][7][8][9] This enthusiasm for newer mechanical devices is tempered by results of Interventional Management of Stroke (IMS) 3, Synthesis Expansion: A Randomized Controlled Trial on Intra-Arterial Versus Intravenous Thrombolysis in Acute Ischemic Stroke (SYNTHESIS), and Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy (MR Rescue) that demonstrate no added advantage of endovascular therapy compared with intravenous tissue-type plasminogen activator (tPA).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] This improvement is reflected in better clinical outcome in studies such as Solitaire With the Intention for Thrombectomy (SWIFT), Thrombectomy Revascularization of Large Vessel Occlusions in Acute Ischemic Stroke (TREVO)-2, and Solitaire FR Thrombectomy for Acute Revascularization (STAR). [6][7][8][9] This enthusiasm for newer mechanical devices is tempered by results of Interventional Management of Stroke (IMS) 3, Synthesis Expansion: A Randomized Controlled Trial on Intra-Arterial Versus Intravenous Thrombolysis in Acute Ischemic Stroke (SYNTHESIS), and Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy (MR Rescue) that demonstrate no added advantage of endovascular therapy compared with intravenous tissue-type plasminogen activator (tPA).…”
mentioning
confidence: 99%
“…Mattle et al 42 reviewed three pilot studies with a total of 29 patients with BAO and reported at least 90% recanalization rate, 31% mortality rate and 45% favorable outcome (mRS 0 -2) among survivors. However, these trials differed in the proportional representation of BAO and pre-post-Solitaire TM treatment method and proportion [43][44][45] . In a recent study, Mordasini et al presented 14 consecutive patients with BAO treated with Solitaire TM with on demand addition of multimodal therapy approaches, such as for example thromboaspiration, IV and/or IA thrombolysis, and percutaneous transluminal angioplasty/permanent stent placement 45 .…”
Section: Mechanical Thrombectomymentioning
confidence: 99%
“…However, these trials differed in the proportional representation of BAO and pre-post-Solitaire TM treatment method and proportion [43][44][45] . In a recent study, Mordasini et al presented 14 consecutive patients with BAO treated with Solitaire TM with on demand addition of multimodal therapy approaches, such as for example thromboaspiration, IV and/or IA thrombolysis, and percutaneous transluminal angioplasty/permanent stent placement 45 . At 3 months, good functional outcome (mRS 0 -2) was observed in 28.6% (4/14) patients and overall mortality was 35.7% (5/14).…”
Section: Mechanical Thrombectomymentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45][46] If we summarize the data from the studies listed in the table, the average recanalization rate is 93.3% to achieve a TICI 2-3/TIMI 2-3 score in a mean of 1.8 passes. Favorable outcome, as measured by mRS score of 0 -2, was achieved in 49.2% of patients at 90 days, with an average mortality rate of about 17.4%.…”
mentioning
confidence: 99%